Expression of virulence factor genes in co-infections with Trueperella pyogenes isolates and other bacterial pathogens; an in vivo study. (March 2022) - Tamai, Iradj Ashrafi; Mohammadzadeh, Abdolmajid; Salehi, Taghi Zahraei; Mahmoodi, Pezhman; Pakbin, Babak
Abstract: Trueperella pyogenes is an opportunistic bacterial pathogen causing several infectious diseases, including metritis, mastitis and abscesses in domestic animals such as dairy cattle. Several virulence proteins are released by T. pyogenes strains contributing to the pathogenic and causing disease potential of this pathogen. So far, many aspects of T. pyogenes pathogenesis are unknown. In this study, expression levels of plo, fimA, nanH and cbpA genes encoding pyolysin, fimbriae, neuraminidase and collagen-binding protein, respectively in T. pyogenes isolated from totally 15 metritis, mastitis and cutaneous abscesses convenience samples in response to co-culture with other pathogens including E. coli, St. dysgalactiae, S. aureus, F. necrophorum and L. plantarum strains in mice study model have been investigated. We found that expression levels of plo, fimA, nanH and cbpA genes in T. pyogenes isolates in response to co-culture with F. necrophorum and E. coli were significantly increased; however, no significant changes was seen in the level of expression of these genes in the isolates in response to co-culture with St. dysgalactiae and S. aureus . Notably, expression of all virulence factor genes was suppressed in T. pyogenes in response to co-culture with L. plantarum . We observed that L. plantarum might be used to prevent infectious diseases caused by T. pyogenes . Highlights: T. pyogenes cause metritis, mastitis and abscesses in dairy cattle. NanH, fimA, plo and cbpA are main virulence factor encoding genes in T. pyogenes . Virulence gene expression is increased in T. pyogenes co-infections. L. plantarum suppress the expression of virulence factors in T. pyogenes .